2006
DOI: 10.1159/000097138
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retention: A Cause of Hyponatremia?

Abstract: Background: Syndrome of inappropriate antidiuretic hormone secretion (SIADH) is the most common cause of hyponatremia in elderly hospitalized patients; however in many patients the etiology remains unclear even after routine investigations. Objective: To report our experience of the association of hyponatremia and urinary retention in elderly hospitalized patients. Patients: Six patients with hyponatremia and urinary retention who were admitted to the geriatric department in our hospital during a four-year per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…Interestingly, similarly to our case, this patient's sodium level normalized after catheterizing the bladder . These reports have suggested that the bladder distention associated with urinary retention can stimulate antidiuretic hormone (ADH) release from the posterior pituitary . It is also postulated that the hypersecretion of ADH may be mediated by the activation of the limbic system caused by the pain associated with bladder distention…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Interestingly, similarly to our case, this patient's sodium level normalized after catheterizing the bladder . These reports have suggested that the bladder distention associated with urinary retention can stimulate antidiuretic hormone (ADH) release from the posterior pituitary . It is also postulated that the hypersecretion of ADH may be mediated by the activation of the limbic system caused by the pain associated with bladder distention…”
Section: Discussionsupporting
confidence: 82%
“…Our patient is considered the first reported pregnant woman developing severe hyponatremia and SIADH secondary to an impacted retroverted uterus. Galperin et al . described five elderly hospitalized patients who developed urinary retention followed by hyponatremia and confirmed SIADH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our patient had chronic retention of urine due to urethral stricture. It has been postulated that chronic urinary retention and subsequent bladder distension can stimulate ADH release from the posterior pituitary, producing a clinical picture similar to SIADH [6,7]. Although urinary retention may improve marginally with medications, surgical management can give a much better relief.…”
Section: Discussionmentioning
confidence: 99%
“…Existen pocos casos descritos en la literatura 3 , 4 , 5 , 6 , 7 . Se cree que la distensión vesical produce una liberación de vasopresina a nivel hipofisario 8 .…”
unclassified